Do social media interventions increase vaccine uptake? - Grosso, Francesca Maria; Baldassarre, Maria Elisabetta; Grosso, Roberto; Di Mauro, Federica; Greco, Chiara; Greco, Silvia; Laforgia, Nicola; Di Mauro, Antonio (Frontiers in Public Health, 2023)
Background: The Italian Mass COVID-19 Vaccination Campaign has included children aged 5–11 as part of the target population since December 2021. One of the biggest challenges to vaccine uptake was vaccine hesitancy among parents and children’s caregivers. Primary care pediatricians (PCP), as the first point of contact between the National Health Service (NHS) and parents/caretakers, initiated various communication strategies to tackle this hesitancy. This study aims to evaluate the impact of a PCP-led social media intervention and a digital reminder service (DRS) on parental hesitancy regarding vaccinating their 5-11 year olds children against COVID-19. Methods: A prospective cohort study was designed, and the chosen target populations were parents and caretakers of children aged 5 to 11. Two PCPs cohorts were recruited. The first group received a social media intervention and a DRS; the second did not. Both cohorts had access to traditional face-to-face and telephone-based counseling. Vaccination coverage rate in the two groups were evaluated. Results: 600 children were enrolled. The exposed cohort (277 patients) received a social media intervention, a DRS, and counselling options (face-to-face and telephone based) whereas the non-exposed cohort (323 patients) received only counseling options. Eighty-nine patients from the exposed cohort did not receive any dose of the COVID-19 vaccine (32.5%), 165 were fully immunized (59.5%), and 23 received only one dose (8.5%). One hundred fifty non-exposed patients did not receive any dose of the Covid-19 vaccine (47%), 147 were fully immunized (45,5%), and 24 only received one dose (7,4%). The difference between the two groups was statistically significant (chi square= 11.5016; p = 0.0006). Conclusion: Social media and DRS interventions had a positive impact on vaccine upatake and may be helpful in tackling vaccine hesitancy. Better-designed studies are needed to corroborate these findings.